2017
DOI: 10.1101/135210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-specific changes in gene expression and delayed sex differentiation in response to estrogen pollution in grayling (Salmonidae)

Abstract: 26The synthetic 17α-ethinylestradiol (EE2) is an estrogenic compound of oral contraceptives 27 and therefore a common pollutant that has been suspected to affect the demography of river-28 dwelling salmonids. We study a population of European grayling (Thymallus thymallus) that 29 suffers from sex ratio distortions. Here we test how ecologically relevant concentrations of 30 EE2 affect sex-specific gene expression around early stages of sex differentiation. We 31 collected gametes from F1s of wild spawners, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Moreover, Brazzola, Chèvre, and Wedekind (2014) exposed embryos of two species of whitefish (Coregonus palaea and C. albellus) to low concentrations of EE2 (from 1 to 100 ng/L) and found EE2 at all concentrations to delay hatching and to reduce embryo survival and growth. Luca et al (in preparation) confirmed the toxicity of EE2 in whitefish and linked it to changes in the metabolic rates during embryogenesis, and Selmoni et al (2017) found EE2 to delay gonad development in grayling larvae (Thymallus thymallus).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, Brazzola, Chèvre, and Wedekind (2014) exposed embryos of two species of whitefish (Coregonus palaea and C. albellus) to low concentrations of EE2 (from 1 to 100 ng/L) and found EE2 at all concentrations to delay hatching and to reduce embryo survival and growth. Luca et al (in preparation) confirmed the toxicity of EE2 in whitefish and linked it to changes in the metabolic rates during embryogenesis, and Selmoni et al (2017) found EE2 to delay gonad development in grayling larvae (Thymallus thymallus).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, Brazzola, Chèvre, and Wedekind () exposed embryos of two species of whitefish ( Coregonus palaea and C. albellus ) to low concentrations of EE2 (from 1 to 100 ng/L) and found EE2 at all concentrations to delay hatching and to reduce embryo survival and growth. Luca et al (in preparation) confirmed the toxicity of EE2 in whitefish and linked it to changes in the metabolic rates during embryogenesis, and Selmoni et al () found EE2 to delay gonad development in grayling larvae ( Thymallus thymallus ).…”
Section: Introductionmentioning
confidence: 99%
“…In accordance, EE2 has been described to change various aspects of development in typical model species (Caldwell et al, 2012, Aris et al, 2014 and to delay early development (Brazzola et al, 2014, Marques da Cunha et al, in prep. ) and sexual differentiation (Selmoni et al, 2017) in salmonids.…”
Section: Discussionmentioning
confidence: 99%